Boshlang’ich Ta’lim Tabiiy Fanlarni O’qitishda Vizual Ta’lim Muhiti - Aslonova Mehriniso Husniddinovna (Periodica Journal, 2024)
This article provides an understanding of the condition of visual education and its elements. At the same time, considerations were made about the role of the visual educational environment in the process of teaching natural sciences
Keywords: Science; visual learning; primary school education; diagramm